Low Risk of Failing Direct-Acting Antivirals in People With Human Immunodeficiency Virus/Hepatitis C Virus From Sub-Saharan Africa or Southeastern Asia: A European Cross-Sectional Study. (30th September 2022) - Isfordink, Cas; Boyd, Anders; Mocroft, Amanda; Kusejko, Katharina; Smit, Colette; de Wit, Stephane; Mahungu, Tabitha; Falconer, Karolin; Wandeler, Gilles; Cavassini, Matthias; Stöckle, Marcel; Schinkel, Janke; et al.
Abstract: Background: Several studies have reported suboptimal efficacy of direct-acting antivirals (DAAs) to treat hepatitis C virus (HCV) subtypes endemic to sub-Saharan Africa (SSA) and Southeastern Asia (SEA). The extent of this issue in individuals with human immunodeficiency virus (HIV)/HCV from SSA or SEA residing in Europe is unknown. Methods: We retrospectively analyzed data from several prospective European cohorts of people living with HIV. We included individuals with HIV/HCV who originated from SSA or SEA, were treated with interferon-free DAAs, and had an available HCV RNA result ≥12 weeks after the end of treatment. The primary outcome was sustained virological response at least 12 weeks after the end of treatment (SVR12 ). Results: Of the 3293 individuals with HIV/HCV treated with DAA and with available SVR12 data, 142 were from SSA (n = 64) and SEA (n = 78). SVR12 was achieved by 60 (94% [95% confidence interval CI, 86%–98%]) individuals from SSA and 76 (97% [95% CI, 92%–99%]) from SEA. The genotypes of the 6 individuals failing DAA treatment were 2, 3a, 3h, 4a, 4c, and 6j. For 2 of the 4 unsuccessfully treated individuals with available sequence data at treatment failure, NS5A resistance-associated substitutions were present (30R/93S in an individual with genotype 4c and 31M in an individual with genotype 6j). Conclusions: SVR12 rates were high in individuals with HIV/HCV residing in Europe and originating from regions where intrinsically NS5A-resistant HCV strains are endemic. HCV elimination for this population in Europe is unlikely to be hampered by suboptimal DAA efficacy. Abstract : We observed reassuring rates of sustained virological response at least 12 weeks after the end of treatment among individuals with HIV/hepatitis C virus from Africa/Asia, suggesting that reduced direct-acting antiviral efficacy is uncommon in this population.